Return to Play and Long-Term Clinical Outcomes after Suture Anchor Repair of Thumb Ulnar Collateral Ligament Injuries in Collegiate Football Athletes. Issue 7 (29th July 2014) - Werner, Brian C.; Hadeed, Michael M.; Lyons, Matthew Lawrence; Diduch, David R.; Chhabra, Abhinav Bobby
Objectives: Thumb ulnar collateral ligament injuries (UCL, gamekeeper's thumb), their surgical treatment and the potential need for prolonged immobilization can significantly damage the careers of collegiate football athletes. Suture anchor fixation may allow quicker return to play with good clinical outcomes but has not been previously studied in this population. The goal of this study is to evaluate return to play and minimum two-year clinical outcomes in collegiate football athletes treated for thumb UCL injuries with suture anchor repair. Methods: Retrospective study. Inclusion criteria were 1) complete rupture of the thumb MCP joint UCL 2) suture anchor repair of UCL 3) collegiate football athlete 4) minimum 2 years postoperative. Data collection included chart review, return to play, and QuickDASH (including work and sport module) outcomes.Skill position players were scheduled for surgery immediately, while non-skilled position players were typically casted until the end of the season and then underwent repair. A single surgeon performed all procedures. Surgical technique was the same for all patients, which included absorbable suture anchor repair of the UCL to the thumb proximal phalanx utilizing two suture anchors. Patients were then immobilized in a thumb spica. Non-skilled position players were cleared for return to play in a cast after sutures were removed. Skilled position players were not cleared until after the cast was removed. Results: A cohort of 18 collegiate football athletes treated with suture anchor thumb UCL repair at minimum 2 years post-procedure was identified. All 18 patients (100%) were available for evaluation at average 6.0 years follow-up (range, 2.5-9.5 yrs). Nine players were skill position players (WR, TE, RB) while the remaining 9 were non-skill positions (OL, DL, LB.) Average age was 19.7 yrs (range, 18-22 yrs). Average time from injury until surgery was 27 days (range 2-105 days). Average return to play for the entire cohort was 5.4 weeks postoperatively (range, 1.5-12.0 weeks). All players returned to at least the same level of play as preoperatively (collegiate). Seven players eventually continued to play professional football. The average QuickDASH score for the entire cohort was 1.2/100 (95% CI 0.40-2.26). Average QuickDASH Work Score was 0.0/100 (95% CI 0.0-0.0) and average QuickDASH Sport Score was 0.7/100 (95% CI 0.0-1.85). Average time to surgery for skill position (n=9) players was 12 days (range 2-26 days) compared to 43 days (range 10-105) in non-skilled (n=9) position players (p = 0.025). Average return to play for skill position players was 7.0 weeks postoperatively (range 4-12 weeks) compared to 3.8 weeks (range 1.5-8.0 weeks) postoperatively in the non-skilled cohort (p = 0.027). There was no difference in average QuickDASH overall score, work score or sport score between the cohorts (Table I). Conclusion: Collegiate football athletes treated for thumb UCL injuries with dual suture anchor repair have quick return to play, reliable return to the same level of play and excellent long-term clinical outcomes. Using the described treatment protocol, skill position players have surgery earlier after injury and return to play later than non-skill position players, without any differences in final level of play or clinical outcomes. Thus, thumb ulnar collateral ligament injuries can be safely and effectively managed by football position demands.